The impact of cohabitation on the character Todd Gilbert in A.S.A Harrison’s The Silent Wife - Fikih Pramudana; Ni Made Widisanti Swetasurya; Shita Dewi Ratih Permatasari (Journal Albion : Journal of English Literature, Language, and Culture, 2025)
The practice of living together without marriage is common in some communities. Marriage serves to legalize the relationship between men and women, allowing them to share a home legally. The term "cohabitation" refers to couples who live together without being married. However, cohabitation can lead to various issues, including infidelity, conflicts, and even dangerous situations. This study employs a descriptive analysis method, utilizing library research techniques grounded in Sigmund Freud's developmental theory (psychoanalysis). In the novel The Silent Wife by A.S.A. Harrison, the consequences of cohabitation manifest as infidelity, disputes among characters, and the deterioration of friendships, ultimately leading to murder. Analyzing the novel through intrinsic and extrinsic approaches reveals that the events affecting the character Todd Gilbert directly result from cohabitation. This situation leads to the development of a new self-concept for Todd and significantly influences his attitude in addressing both internal and external conflicts.